2010
DOI: 10.1111/j.1755-3768.2010.3158.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of uveitic glaucoma

Abstract: Purpose Secondary glaucoma is a difficult and frequent complication of uveitis. The aim of this study is to describe the results of surgery in uveitic glaucoma and to identify situations linked to a high risk of failure of the surgery. Methods Retrospective observational study. Clinical and surgical data from 27 cases of uveitic glaucoma that underwent glaucoma surgery over a period of 9 years were collected. Results The main diagnosis and aetiology were anterior uveitis (61.90%) and herpes (38.10%) respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Trabeculectomy surgery for uveitic glaucoma is known to have worse prognosis compared with surgery for POAG . Overall qualified success rate of 67% for trabeculectomy in our study is comparable with those found in similar studies for uveitic glaucoma (50–85%) . Kaburaki et al showed that in eyes with inactive uveitis, success rate was 65% at 5 years and has higher rate of ocular hypotony after operation compared to POAG .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Trabeculectomy surgery for uveitic glaucoma is known to have worse prognosis compared with surgery for POAG . Overall qualified success rate of 67% for trabeculectomy in our study is comparable with those found in similar studies for uveitic glaucoma (50–85%) . Kaburaki et al showed that in eyes with inactive uveitis, success rate was 65% at 5 years and has higher rate of ocular hypotony after operation compared to POAG .…”
Section: Discussionsupporting
confidence: 86%
“…Mixed findings were reported in the literature with regard to the effect that activity of uveitis at the time of surgery has on surgical outcomes. A small study with 21 cases of uveitic glaucoma concluded that active uveitis at the time of surgery is a significant risk factor for failure; however, there were only two cases with active uveitis at the time of surgery in that series . In larger studies from Japan by Kaburaki et al and Shimizu et al showed that the presence of inflammation at the time of surgery was not a significant risk factor for the outcome of trabeculectomy but postoperative relapse of inflammation was significant .…”
Section: Discussionmentioning
confidence: 93%